Arabic Argumentation: Presentation or Proof - Al-Sharafi, Abdul Gabbar; Majed Khader, Mohammad; Hamza Al-Sioufy, Mohamad; Ahmed, Mohamed; Al-Zawqari, Ali (Informal Logic)

(untitled) (Informal Logic, 2025)
Arabic argumentation is often described as relying on repetition and coordination in contrast to Western argumentation, which emphasizes syllogism, proof, and dialectic. However, previous studies on this topic were based on a limited and unrepresentative corpus. This study seeks to verify these claims using a contemporary corpus of 110 Arabic competitive debates, comprising approximately 515,793 words. A hybrid argumentation annotation model, combining Aristotle’s rhetorical appeals (logos, ethos, pathos) and Toulmin’s model of argument structure, was developed for analysis. The findings reveal a high prevalence of logos compared to ethos and pathos, with relatively minimal reliance on repetition. Arabic argumentation emerges as diverse rather than monolithic, incorporating both inferential reasoning and rhetorical repetition. This study also highlights the influence of genre on rhetorical strategy use, calling for further research on genre-specific Arabic argumentation.